PENYULUHAN PENGGUNAAN HAND SANITIZER DAN CUCI TANGAN YANG BENAR PADA SISWA SD N 1 DEPOK - Maulita Saraswati; Wahyu Purwanjani; Alya Iffa Naila; Wahyu Esti Anggita (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2023)
Background: One way that is believed to be effective in preventing the transmission of the corona virus is to diligently wash your hands with soap in running water. In fact, soap is said to be more effective than hand sanitizer, because it can eliminate bacteria and viruses on the surface of the skin. Washing hands is a process of removing dirt that sticks to the hands mechanically using detergent containing antiseptic ingredients and running water, starting from the fingertips to the elbows and arms in a certain way according to needs. Things to remember when washing your hands: 1) If it is clearly visible or contaminated with protein-containing materials, hands should be washed using detergent and running water. 2) If hands are not clearly dirty or contaminated, alcohol-based antiseptics should be used to decontaminate hands regularly. 3) Before starting an activity, make sure your hands are dry. Purpose: Increasing student awareness of the importance of maintaining hand hygiene through the use of hand sanitizers and proper hand washing as an effort to prevent the spread of disease and infection. Method: The method used is quantitative descriptive, where the resource person provides material on how to use hand sanitizer and how to wash hands properly through power point media. The presentation of material on how to wash hands contains why you should wash your hands, when is the right time to wash your hands, the causes of the spread of infection due to not washing your hands, the duration of washing your hands with hand sanitizer or soap and how to wash your hands. Participants in this community service are students of SD Negeri 1 Depok. After the delivery of the material, a question and answer session was held, where training participants were given the opportunity to ask questions about the material that had been presented. The speaker provided answers that were appropriate and easy for participants to understand. Results: The socialization activity of the use of hand sanitizers and proper hand washing at SD Negeri 1 Depok went smoothly without any obstacles, the  activity was well received by teachers and students. The results of the socialization that had been carried out showed a significant increase in knowledge among participants about the importance of maintaining hand hygiene by using hand sanitizers and washing hands using soap and running water. Participants also gained an understanding of the steps for using hand sanitizers and proper hand washing from the socialization activities that had been carried out. Conclusion: The socialization activities for the use of hand sanitizers and proper hand washing went well and achieved the desired goal, namely increasing participants' knowledge about the importance of maintaining hand hygiene in order to minimize the risk of spreading viruses and diseases using hand sanitizers and washing hands with soap and running water or clean water.